A low-refractive anti-reflection film structure of a photovoltaic cell, a preparation method and a cell

By adjusting the Si to N ratio of SiNx layer in the photovoltaic cell anti-reflection film, the refractive index is reduced without affecting the passivation performance, the problem of refractive index adjustment in the prior art affecting the efficiency of the battery is solved, and efficient light absorption and short-circuit current increase are achieved.

CN119108438BActive Publication Date: 2025-03-25MIANYANG XINHAO NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411227050.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-03-25
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

The prior art reduces the refractive index by adjusting the thickness of the anti-reflective film, but this will affect the passivation performance of the battery and make it difficult to improve the battery efficiency as a whole.

Method used

By changing the ratio of Si to N in the SiNx layer, adjusting the nitrogen-silicon ratio of the SiNx layer in the anti-reflection film, the overall refractive index of the SiNx-SiONx-SiO2 anti-reflection film on the front of the battery is reduced without changing the thickness of the film layer.

Benefits of technology

The overall refractive index of the anti-reflection film is achieved, the absorption of light is increased, the short-circuit current of the battery is greatly increased, and the passivation performance of the battery is retained, so that the open circuit voltage is not changed much.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119108438B_ABST
    Figure CN119108438B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of photovoltaic technology, and discloses a low-refractive anti-reflection film structure of a photovoltaic cell, a preparation method and a cell. The anti-reflection film structure comprises a first SiN film sequentially deposited from bottom to top. x Thin film layer, second SiN x Thin film layer, third SiN x Thin film layer, fourth SiN x Thin film layer; the first SiN x The nitrogen-silicon ratio of the thin film layer is 3.33; the second SiN x The nitrogen-silicon ratio of the thin film layer is 6.16; the third SiN x The nitrogen-silicon ratio of the thin film layer is 9.49; the fourth SiN x The nitrogen-silicon ratio of the thin film layer is 9.49. x The ratio of Si to N in the layer can make the SiN on the front of the cell smaller without changing the thickness of the anti-reflection film. x ‑SiON x ‑SiO 2 The overall refractive index of the anti-reflection film is reduced, thereby increasing the absorption of light and significantly increasing the short-circuit current of the battery. At the same time, since there is no need to adjust the film thickness, the passivation performance of the battery can be retained, so that the open-circuit voltage of the battery does not change much.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photovoltaic technology, and in particular to a low-refractive anti-reflection film structure of a photovoltaic cell, a preparation method and a cell. Background Art

[0002] Receiving sufficient light is a key factor in improving the efficiency of solar cells. Adequate light exposure can stimulate more electron transitions, thereby increasing the battery's light absorption rate and the battery's short-circuit current, thereby improving the battery's efficiency.

[0003] The current ways to increase battery lighting are: 1. Reduce the grid line width to increase the light irradiation area; 2. Increase the specific surface area of ​​the velvet surface to increase the distance light travels on the velvet surface; 3. Increase the reflectivity of the back of the battery to make it less likely for light to escape from the back of the battery; 4. Reduce the refractive index of the front anti-reflection film to allow more light to be absorbed by the battery.

[0004] To reduce the refractive index of the front anti-reflection film, the commonly used method at present is to reduce the refractive index of the film layer by adjusting the thickness of the film layer. However, the adjustment of the thickness of the film layer will affect the passivation performance of the battery, making it difficult to achieve the goal of improving the overall battery efficiency.

[0005] In view of this, this application is hereby filed. Summary of the invention

[0006] The problem of the prior art is that the refractive index of the film layer is reduced by adjusting the thickness of the anti-reflection film, but the adjustment of the film thickness will affect the passivation performance of the battery, making it difficult to achieve the purpose of improving the overall battery efficiency. A low-refractive anti-reflection film structure of a photovoltaic cell, a preparation method and a battery are provided. By changing the SiN x The ratio of Si to N in the layer can make the SiN on the front of the cell smaller without changing the thickness of the anti-reflection film. x -SiON x -The overall refractive index of the SiO2 anti-reflection film is reduced, thereby increasing the absorption of light and significantly increasing the short-circuit current of the battery. At the same time, since there is no need to adjust the film thickness, the passivation performance of the battery can be retained, so that the open-circuit voltage of the battery does not change much.

[0007] The present invention is achieved through the following technical solutions:

[0008] In a first aspect, the present invention provides a low-refractive anti-reflection film structure applied to a photovoltaic cell, including an anti-reflection film structure arranged on the front side of a cell, the anti-reflection film structure comprising a first SiN film deposited sequentially from bottom to top, x Thin film layer, second SiN x Thin film layer, third SiN x Thin film layer, fourth SiN x Thin film layer;

[0009] The first SiN x The nitrogen-to-silicon ratio of the film layer is 3.33;

[0010] The second SiN x The nitrogen-to-silicon ratio of the film layer is 6.16;

[0011] The third SiN x The nitrogen-to-silicon ratio of the film layer is 9.49;

[0012] The fourth SiN x The nitrogen to silicon ratio of the thin film layer is 9.49.

[0013] In a specific embodiment, the anti-reflection film structure further includes sequentially deposited on the fourth SiN x SiON on thin film layer x Thin film and SO2 thin film.

[0014] In a second aspect, the present invention provides a method for preparing a low-refractive anti-reflection film structure for a photovoltaic cell, wherein the anti-reflection film structure comprises a first SiN film deposited sequentially from bottom to top; x Thin film layer, second SiN x Thin film layer, third SiN x Thin film layer, fourth SiN x Thin film layer;

[0015] The first SiN x The deposition process of the thin film layer is:

[0016] At a time of 35-45s, the SiH4 flow rate was 2800sccm, the NH3 flow rate was 9335sccm, and the pressure was constant at 1650mttor;

[0017] Deposition was performed under the conditions of time 25-35s, power 1 of 12500-13500W, power 2 of 13500-14500W, pulse on for 50ms, and pulse off for 600ms.

[0018] In a specific embodiment, the second SiN x The deposition process of the thin film layer is:

[0019] At a time of 35-45s, the SiH4 flow rate was 1700sccm, the NH3 flow rate was 10465sccm, and the pressure was constant at 1700mttor;

[0020] Deposition was performed under the conditions of time of 150-160s, power 1 of 15500-16500W, power 2 of 16500-17500W, pulse on of 50ms, and pulse off of 600ms.

[0021] In a specific embodiment, the third SiN x The deposition process of the thin film layer is:

[0022] Deposition was carried out under the conditions of a time of 195-205s, a SiH4 flow rate of 1150sccm, a NH3 flow rate of 10915sccm, a pressure of 1700mttor, a power of 15500-16500W, a power of 16500W-17500W, a pulse on time of 50ms, and a pulse off time of 600ms.

[0023] In a specific embodiment, the fourth SiN x The deposition process of the thin film layer is:

[0024] Deposition was performed under the conditions of a time of 250-260s, a SiH4 flow rate of 1150sccm, a NH3 flow rate of 10915sccm, a pressure of 1800mttor, a power of 15500-16500W, a power of 16500-17500W, a pulse on time of 50ms, and a pulse off time of 600ms.

[0025] In a specific embodiment, the anti-reflection film structure further comprises SiON x Thin film, the SiON x The film includes a first SiON x Thin film layer and second SiON x Thin film layer;

[0026] The first SiON was deposited at a time of 15-25 s, a SiH4 flow rate of 1200 sccm, an NH3 flow rate of 5200 sccm, a N2O flow rate of 5200 sccm, and a constant pressure of 1300 mttor; the first SiON was deposited at a time of 120-130 s, a power of 14000-14400 W, a power of 14000-14400 W, a pulse on of 50 ms, and a pulse off of 1000 ms. x Thin film layer;

[0027] The second SiON was deposited at a time of 140-150s, a SiH4 flow rate of 900sccm, an NH3 flow rate of 5200sccm, a N2O flow rate of 8935sccm, a pressure of 1300mttor, a power of 14000-14400W, a power of 14000-14400W, a pulse on of 50ms, and a pulse off of 1000ms. x Thin film layer.

[0028] In a specific embodiment, the anti-reflection film structure further includes an SO2 thin film layer, and the deposition process of the SO2 thin film layer is:

[0029] The deposition time was 15-25 s, the SiH4 flow rate was 900 sccm, the N2O flow rate was 11735 sccm, and the pressure was constant at 1000 mttor; the deposition time was 90-100 s, the power one was 14000-14400 W, the power two was 14000-14400 W, the pulse was on for 50 ms, and the pulse was off for 1000 ms.

[0030] In a specific embodiment, in the anti-reflection film structure deposition process, the temperature conditions are: from temperature zone one to temperature zone nine are 460-465°C; 445-450°C; 440-445°C; 440-445°C; 445-450°C; 445-450°C; 440-445°C; 440-435°C; 425-430°C respectively.

[0031] In a third aspect, the present invention further provides a high-performance photovoltaic cell, comprising the anti-reflection film structure or the anti-reflection film structure produced by the method.

[0032] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0033] 1. A low-refractive anti-reflection film structure, a preparation method and a cell for a photovoltaic cell provided in an embodiment of the present invention, by changing the SiN x The ratio of Si to N in the layer can make the SiN on the front of the cell x -SiON x -The overall refractive index of the SiO2 anti-reflection film is reduced to 2.028-2.039, thereby increasing the absorption of light and significantly increasing the short-circuit current of the battery;

[0034] 2. A low-refractive anti-reflection film structure, a preparation method and a cell for a photovoltaic cell provided in an embodiment of the present invention, by increasing the SiN x The nitrogen-silicon ratio of the layer can reduce the overall refractive index in the anti-reflection film, thereby increasing the number of electron transitions in the battery. Sufficient electrons are more conducive to electrode collection, thereby increasing the short-circuit current to 56mA.

[0035] 3. A low-refractive anti-reflection film structure, preparation method and cell for a photovoltaic cell provided in an embodiment of the present invention. Since the silicon content in the anti-reflection film on the front side of the cell is reduced, the electrode contact of the cell is also improved to a certain extent, and the FF is increased, thereby obtaining a higher efficiency improvement of 0.136%;

[0036] 4. The low-refractive anti-reflection film structure, preparation method and battery of a photovoltaic cell provided in an embodiment of the present invention do not need to adjust the film thickness compared to the existing anti-reflection film, can retain the passivation performance of the battery, and make the open-circuit voltage of the battery change little. In addition, silver ions can more easily pass through the anti-reflection film, so that the battery has better electrode contact performance, thereby improving the fill factor of the battery and ultimately achieving high battery efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 A low-refractive anti-reflection film structure provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0039] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0040] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to one of ordinary skill in the art that these specific details need not be employed to practice the present invention. In other embodiments, in order to avoid obscuring the present invention, well-known materials or methods are not specifically described.

[0041] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment," "an embodiment," "an example," or "an example" appearing in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any suitable combination and / or subcombination. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0042] The current ways to increase battery lighting are: 1. Reduce the grid line width to increase the light irradiation area; 2. Increase the specific surface area of ​​the velvet surface to increase the distance light travels on the velvet surface; 3. Increase the reflectivity of the back of the battery to make it less likely for light to escape from the back of the battery; 4. Reduce the refractive index of the front anti-reflection film to allow more light to be absorbed by the battery.

[0043] To reduce the refractive index of the front anti-reflection film, the commonly used method at present is to reduce the refractive index of the film layer by adjusting the thickness of the film layer. However, the adjustment of the thickness of the film layer will affect the passivation performance of the battery, making it difficult to achieve the goal of improving the overall battery efficiency.

[0044] To solve the above problems:

[0045] First, as Figure 1 As shown, the present invention provides a low-refractive anti-reflection film structure applied to a photovoltaic cell, including an anti-reflection film structure arranged on the front side of a cell, the anti-reflection film structure comprising a first SiN x Thin film layer, second SiN x Thin film layer, third SiN x Thin film layer, fourth SiN x Thin film layer;

[0046] The first SiN x The nitrogen-to-silicon ratio of the film layer is 3.33;

[0047] The second SiN x The nitrogen-to-silicon ratio of the film layer is 6.16;

[0048] The third SiN x The nitrogen-to-silicon ratio of the film layer is 9.49;

[0049] The fourth SiN x The nitrogen to silicon ratio of the thin film layer is 9.49.

[0050] In a specific embodiment, the anti-reflection film structure further includes sequentially deposited on the fourth SiN x SiON on thin film layer x Thin film and SO2 thin film.

[0051] In a second aspect, the present invention provides a method for preparing a low-refractive anti-reflection film structure for a photovoltaic cell, wherein the anti-reflection film structure comprises a first SiN film deposited sequentially from bottom to top; x Thin film layer, second SiN x Thin film layer, third SiN x Thin film layer, fourth SiN x Thin film layer, first SiON x Thin film layer, second SiON x thin film layer and SO2 thin film layer; the deposition temperatures of the anti-reflection film structure from temperature zone one to temperature zone nine are 460-465°C; 445-450°C; 440-445°C; 440-445°C; 445-450°C; 445-450°C; 440-445°C; 440-435°C; 425-430°C.

[0052] The first SiN x The deposition process of the thin film layer is:

[0053] The deposition was carried out under the conditions of 35-45 s, 2800 sccm SiH4 flow rate, 9335 sccm NH3 flow rate and constant pressure at 1650 mttor; the deposition was carried out under the conditions of 25-35 s, 12500-13500 W power 1, 13500-14500 W power 2, 50 ms pulse on and 600 ms pulse off.

[0054] The second SiN x The deposition process of the thin film layer is:

[0055] The deposition time was 35-45s, the SiH4 flow rate was 1700sccm, the NH3 flow rate was 10465sccm, and the pressure was constant at 1700mttor; the deposition time was 150-160s, the power one was 15500-16500W, the power two was 16500-17500W, the pulse was on for 50ms, and the pulse was off for 600ms.

[0056] The third SiN x The deposition process of the thin film layer is:

[0057] Deposition was carried out under the conditions of a time of 195-205s, a SiH4 flow rate of 1150sccm, a NH3 flow rate of 10915sccm, a pressure of 1700mttor, a power of 15500-16500W, a power of 16500W-17500W, a pulse on time of 50ms, and a pulse off time of 600ms.

[0058] The fourth SiN x The deposition process of the thin film layer is:

[0059] Deposition was performed under the conditions of a time of 250-260s, a SiH4 flow rate of 1150sccm, a NH3 flow rate of 10915sccm, a pressure of 1800mttor, a power of 15500-16500W, a power of 16500-17500W, a pulse on time of 50ms, and a pulse off time of 600ms.

[0060] The first SiON x The deposition process of the thin film layer is:

[0061] The deposition time was 15-25s, the SiH4 flow rate was 1200sccm, the NH3 flow rate was 5200sccm, the N2O flow rate was 5200sccm, and the pressure was constant at 1300mttor; the deposition time was 120-130s, the power one was 14000-14400W, the power two was 14000-14400W, the pulse was on for 50ms, and the pulse was off for 1000ms.

[0062] Second SiON x The deposition process of the thin film layer is:

[0063] Deposition was carried out under the conditions of 140-150s, 900sccm SiH4 flow rate, 5200sccm NH3 flow rate, 8935sccm N2O flow rate, 1300mttor pressure, 14000-14400W power 1, 14000-14400W power 2, 50ms pulse on, 1000ms pulse off.

[0064] The deposition process of the SO2 thin film layer is as follows:

[0065] The deposition time was 15-25 s, the SiH4 flow rate was 900 sccm, the N2O flow rate was 11735 sccm, and the pressure was constant at 1000 mttor; the deposition time was 90-100 s, the power one was 14000-14400 W, the power two was 14000-14400 W, the pulse was on for 50 ms, and the pulse was off for 1000 ms.

[0066] In a third aspect, the present invention further provides a high-performance photovoltaic cell, comprising the anti-reflection film structure or the anti-reflection film structure produced by the method.

[0067] Example 1

[0068] The embodiment of the present invention provides a method for preparing a low-refractive anti-reflection film structure applied to a photovoltaic cell, comprising the following steps:

[0069] (1) All temperatures in the process from temperature zone 1 to temperature zone 9 are 460-465°C; 445-450°C; 440-445°C; 440-445°C; 445-450°C; 445-450°C; 440-445°C; 440-435°C; 425-430°C.

[0070] (2) The first layer of SiN was deposited at a time of 35-45 s, a SiH4 flow rate of 2800 sccm, an NH3 flow rate of 9335 sccm, and a pressure of 1650 mttor. The first layer of SiN was deposited at a time of 25-35 s, a power of 12500-13500 W, a power of 13500-14500 W, a pulse on of 50 ms, and a pulse off of 600 ms. x Thin film layer.

[0071] (3) The second layer of SiN was deposited at a time of 35-45 s, a SiH4 flow rate of 1700 sccm, an NH3 flow rate of 10465 sccm, and a constant pressure of 1700 mttor. The second layer of SiN was deposited at a time of 150-160 s, a power of 15500-16500 W, a power of 16500-17500 W, a pulse on of 50 ms, and a pulse off of 600 ms. x Thin film layer.

[0072] (4) The third layer of SiN was deposited at a time of 195-205 s, a SiH4 flow rate of 1150 sccm, an NH3 flow rate of 10915 sccm, a pressure of 1700 mttor, a power of 15500-16500 W, a power of 16500 W-17500 W, a pulse on of 50 ms, and a pulse off of 600 ms. x Thin film layer.

[0073] (5) The fourth layer of SiN was deposited under the conditions of 250-260 s, SiH4 flow rate of 1150 sccm, NH3 flow rate of 10915 sccm, pressure of 1800 mttor, power 1 of 15500-16500 W, power 2 of 16500-17500 W, pulse on for 50 ms, pulse off for 600 ms. x Thin film layer.

[0074] (6) The fifth layer of SiON was deposited at a time of 15-25 s, a SiH4 flow rate of 1200 sccm, an NH3 flow rate of 5200 sccm, a N2O flow rate of 5200 sccm, and a pressure of 1300 mttor. The fifth layer of SiON was deposited at a time of 120-130 s, a power of 14000-14400 W, a power of 2 of 14000-14400 W, a pulse on of 50 ms, and a pulse off of 1000 ms. x Thin film layer.

[0075] (7) The sixth layer of SiON was deposited at a time of 140-150 s, a SiH4 flow rate of 900 sccm, an NH3 flow rate of 5200 sccm, a N2O flow rate of 8935 sccm, a pressure of 1300 mttor, a power of 14000-14400 W, a power of 14000-14400 W, a pulse on of 50 ms, and a pulse off of 1000 ms. x Thin film layer.

[0076] (8) The seventh SiO2 thin film layer was deposited at a time of 15-25 s, a SiH4 flow rate of 900 sccm, a N2O flow rate of 11735 sccm, and a constant pressure of 1000 mttor. The seventh SiO2 thin film layer was deposited at a time of 90-100 s, a power of 14000-14400 W, a power of 2 of 14000-14400 W, a pulse on of 50 ms, and a pulse off of 1000 ms.

[0077] The SiN prepared in this example x The performance test of thin film battery is shown in Table 1 below.

[0078] Table 1

[0079]

[0080] Example 2

[0081] The embodiment of the present invention provides a method for preparing a low-refractive anti-reflection film structure applied to a photovoltaic cell, comprising the following steps:

[0082] (1) All temperatures in the process from temperature zone 1 to temperature zone 9 are 460-465°C; 445-450°C; 440-445°C; 440-445°C; 445-450°C; 445-450°C; 440-445°C; 440-435°C; 425-430°C.

[0083] (2) The first layer of SiN was deposited at a time of 35-45 s, a SiH4 flow rate of 2800 sccm, an NH3 flow rate of 9335 sccm, and a pressure of 1650 mttor. The first layer of SiN was deposited at a time of 25-35 s, a power of 12500-13500 W, a power of 13500-14500 W, a pulse on of 50 ms, and a pulse off of 600 ms. x Thin film layer.

[0084] (3) The second layer of SiN was deposited at a time of 35-45 s, a SiH4 flow rate of 1700 sccm, an NH3 flow rate of 10465 sccm, and a constant pressure of 1700 mttor. The second layer of SiN was deposited at a time of 150-160 s, a power of 15500-16500 W, a power of 16500-17500 W, a pulse on of 50 ms, and a pulse off of 600 ms. x Thin film layer.

[0085] (4) The third layer of SiN was deposited at a time of 195-205 s, a SiH4 flow rate of 1150 sccm, an NH3 flow rate of 10915 sccm, a pressure of 1700 mttor, a power of 15500-16500 W, a power of 16500 W-17500 W, a pulse on of 50 ms, and a pulse off of 600 ms. x Thin film layer.

[0086] (5) The fourth layer of SiN was deposited under the conditions of 250-260 s, SiH4 flow rate of 1150 sccm, NH3 flow rate of 10915 sccm, pressure of 1800 mttor, power 1 of 15500-16500 W, power 2 of 16500-17500 W, pulse on for 50 ms, pulse off for 600 ms. x Thin film layer.

[0087] (6) The fifth layer of SiON was deposited at a time of 15-25 s, a SiH4 flow rate of 1200 sccm, an NH3 flow rate of 5200 sccm, a N2O flow rate of 5200 sccm, and a pressure of 1300 mttor. The fifth layer of SiON was deposited at a time of 120-130 s, a power of 14000-14400 W, a power of 2 of 14000-14400 W, a pulse on of 50 ms, and a pulse off of 1000 ms. x Thin film layer.

[0088] (7) The sixth layer of SiON was deposited at a time of 140-150 s, a SiH4 flow rate of 900 sccm, an NH3 flow rate of 5200 sccm, a N2O flow rate of 8935 sccm, a pressure of 1300 mttor, a power of 14000-14400 W, a power of 14000-14400 W, a pulse on of 50 ms, and a pulse off of 1000 ms. x Thin film layer.

[0089] (8) The seventh SiO2 thin film layer was deposited at a time of 15-25 s, a SiH4 flow rate of 900 sccm, a N2O flow rate of 11735 sccm, and a constant pressure of 1000 mttor. The seventh SiO2 thin film layer was deposited at a time of 90-100 s, a power of 14000-14400 W, a power of 2 of 14000-14400 W, a pulse on of 50 ms, and a pulse off of 1000 ms.

[0090] The SiN prepared in this example x The performance test of thin film battery is shown in Table 2 below.

[0091] Table 2

[0092]

[0093] Comparative Example

[0094] This comparative example provides a method for preparing an anti-reflection film structure, comprising the following steps:

[0095] (1) All temperatures in the process from temperature zone 1 to temperature zone 9 are 460-465°C; 445-450°C; 440-445°C; 440-445°C; 445-450°C; 445-450°C; 440-445°C; 440-435°C; 425-430°C.

[0096] (2) The first layer of SiN was deposited at a time of 35-45 s, a SiH4 flow rate of 2800 sccm, an NH3 flow rate of 9335 sccm, and a pressure of 1650 mttor. The first layer of SiN was deposited at a time of 25-35 s, a power of 12500-13500 W, a power of 13500-14500 W, a pulse on of 50 ms, and a pulse off of 600 ms. x Thin film layer.

[0097] (3) The second layer of SiN was deposited at a time of 35-45 s, a SiH4 flow rate of 2800 sccm, an NH3 flow rate of 9335 sccm, and a constant pressure of 1700 mttor. The second layer of SiN was deposited at a time of 95-105 s, a power of 15500-16500 W, a power of 2 of 16500-17500 W, a pulse on of 50 ms, and a pulse off of 750 ms. x Thin film layer.

[0098] (4) The third layer of SiN was deposited at a time of 255-265 s, a SiH4 flow rate of 2000 sccm, an NH3 flow rate of 10665 sccm, a pressure of 1700 mttor, a power of 15500-16500 W, a power of 16500 W-17500 W, a pulse on time of 50 ms, and a pulse off time of 650 ms.x Thin film layer.

[0099] (5) The fourth layer of SiN was deposited at a time of 265-275 s, a SiH4 flow rate of 1400 sccm, an NH3 flow rate of 10665 sccm, a pressure of 1800 mttor, a power of 15500-16500 W, a power of 16500-17500 W, a pulse on time of 50 ms, and a pulse off time of 600 ms. x Thin film layer.

[0100] (6) The fifth layer of SiON was deposited at a time of 15-25 s, a SiH4 flow rate of 1200 sccm, an NH3 flow rate of 5200 sccm, a N2O flow rate of 5200 sccm, and a pressure of 1300 mttor. The fifth layer of SiON was deposited at a time of 120-130 s, a power of 14000-14400 W, a power of 2 of 14000-14400 W, a pulse on of 50 ms, and a pulse off of 1000 ms. x Thin film layer.

[0101] (7) The sixth layer of SiON was deposited at a time of 140-150 s, a SiH4 flow rate of 900 sccm, an NH3 flow rate of 5200 sccm, a N2O flow rate of 8935 sccm, a pressure of 1300 mttor, a power of 14000-14400 W, a power of 14000-14400 W, a pulse on of 50 ms, and a pulse off of 1000 ms. x Thin film layer.

[0102] (8) The seventh SiO2 thin film layer was deposited at a time of 15-25 s, a SiH4 flow rate of 900 sccm, a N2O flow rate of 11735 sccm, and a constant pressure of 1000 mttor. The seventh SiO2 thin film layer was deposited at a time of 90-100 s, a power of 14000-14400 W, a power of 2 of 14000-14400 W, a pulse on of 50 ms, and a pulse off of 1000 ms.

[0103] The silicon oxynitride and silicon oxide deposition processes in this comparative example are the same as steps (6) to (8) of Examples 1 and 2. The performance test of the prepared cell is shown in Table 3 below.

[0104] Table 3

[0105]

[0106] In the comparative example, the overall nitrogen-silicon ratio of the anti-reflection film prepared by the conventional process is only 4.44, the refractive index of the obtained anti-reflection film is 2.084, and the overall thickness of the anti-reflection film is 78 nm.

[0107] In the embodiments 1 and 2 of the present invention, the SiN x The nitrogen-silicon ratio in the thin film layer makes the overall nitrogen-silicon ratio of the anti-reflection film reach 6.12, which is greatly improved compared with the comparative example. The refractive index of the anti-reflection film obtained in Example 1 is 2.039, and the refractive index of the anti-reflection film obtained in Example 2 is 2.028, which is greatly improved compared with the conventional process. At the same time, the thickness of the anti-reflection film obtained is 76nm and 73nm, respectively, which is basically the same as the film thickness of the comparative example, and will not affect the passivation effect of the battery. In addition, it can be seen from the data in Table 1, Table 2 and Table 3 that the short-circuit current Isc and the fill factor FF of the battery cell prepared in the embodiment of the present invention are increased compared with the comparative example, thereby improving the efficiency of the photovoltaic cell.

[0108] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a low-refractive anti-reflection film structure for photovoltaic cells, characterized in that: The anti-reflection film structure includes a first SiN film deposited sequentially from bottom to top x Thin film layer, second SiN x Thin film layer, third SiN x Thin film layer, fourth SiN x Thin film layer; The first SiN x The nitrogen-to-silicon ratio of the film layer is 3.33; The second SiN x The nitrogen-to-silicon ratio of the film layer is 6.16; The third SiN x The nitrogen-to-silicon ratio of the film layer is 9.49; The fourth SiN x The nitrogen-to-silicon ratio of the film layer is 9.49; The first SiN x The deposition process of the thin film layer is: At a time of 35-45s, the SiH4 flow rate was 2800sccm, the NH3 flow rate was 9335sccm, and the pressure was constant at 1650mttor; Deposition was performed under the conditions of time 25-35s, power 1 of 12500-13500W, power 2 of 13500-14500W, pulse on for 50ms, and pulse off for 600ms.

2. The method for preparing a low-refractive anti-reflection film structure for photovoltaic cells according to claim 1, characterized in that: The second SiN x The deposition process of the thin film layer is: At a time of 35-45s, the SiH4 flow rate was 1700sccm, the NH3 flow rate was 10465sccm, and the pressure was constant at 1700mttor; Deposition was performed under the conditions of time of 150-160s, power 1 of 15500-16500W, power 2 of 16500-17500W, pulse on of 50ms, and pulse off of 600ms.

3. The method for preparing a low-refractive anti-reflection film structure for photovoltaic cells according to claim 1, characterized in that: The third SiN x The deposition process of the thin film layer is: Deposition was carried out under the conditions of a time of 195-205s, a SiH4 flow rate of 1150sccm, a NH3 flow rate of 10915sccm, a pressure of 1700mttor, a power of 15500-16500W, a power of 16500W-17500W, a pulse on time of 50ms, and a pulse off time of 600ms.

4. The method for preparing a low-refractive anti-reflection film structure for photovoltaic cells according to claim 1, characterized in that: The fourth SiN x The deposition process of the thin film layer is: Deposition was performed under the conditions of a time of 250-260s, a SiH4 flow rate of 1150sccm, a NH3 flow rate of 10915sccm, a pressure of 1800mttor, a power of 15500-16500W, a power of 16500-17500W, a pulse on time of 50ms, and a pulse off time of 600ms.

5. The method for preparing a low-refractive anti-reflection film structure for photovoltaic cells according to claim 1, characterized in that: The anti-reflection film structure further comprises SiON x Thin film, the SiON x The film includes a first SiON x Thin film layer and second SiON x Thin film layer; The first SiON was deposited at a time of 15-25 s, a SiH4 flow rate of 1200 sccm, an NH3 flow rate of 5200 sccm, a N2O flow rate of 5200 sccm, and a constant pressure of 1300 mttor; the first SiON was deposited at a time of 120-130 s, a power of 14000 to 14400 W, a power of 14000 to 14400 W, a pulse on of 50 ms, and a pulse off of 1000 ms. x Thin film layer; The second SiON was deposited at a time of 140-150s, a SiH4 flow rate of 900sccm, an NH3 flow rate of 5200sccm, a N2O flow rate of 8935sccm, a pressure of 1300mttor, a power of 14000∼14400W, a power of 14000∼14400W, a pulse on of 50ms, and a pulse off of 1000ms. x Thin film layer.

6. The method for preparing a low-refractive anti-reflection film structure for photovoltaic cells according to claim 1, characterized in that: The anti-reflection film structure further includes an SO2 thin film layer, and the deposition process of the SO2 thin film layer is: The deposition time was 15-25 s, the SiH4 flow rate was 900 sccm, the N2O flow rate was 11735 sccm, and the pressure was constant at 1000 mttor. The deposition time was 90-100 s, the power one was 14000∼14400 W, the power two was 14000∼14400 W, the pulse was on for 50 ms, and the pulse was off for 1000 ms.

7. The method for preparing a low-refractive anti-reflection film structure for photovoltaic cells according to claim 1, characterized in that: In the anti-reflection film structure deposition process, the temperature conditions are: from temperature zone one to temperature zone nine are 460∼465℃; 445∼450℃; 440∼445℃; 440∼445℃; 445∼450℃; 445∼450℃; 440∼445℃; 440∼435℃; 425∼430℃ respectively.

8. A high-performance photovoltaic cell, characterized in that: The invention comprises an anti-reflection film structure obtained by the preparation method described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Solar cell front multilayer antireflection film, preparation method thereof and cell

    CN111739949A

  • Preparation method of laminated antireflection film of solar cell

    CN112713216A